Protocol for a multicentric, double-blind, randomised controlled trial of hyperbaric oxygen therapy (HBOT) versus sham for treating vaso-occlusive crisis (VOC) in sickle cell disease (SCD) in patients aged 8 years or older (HBOT-SCD study) - Thomas Agoritsas; Alain Gervaix; Sylvain Boet; Pierre Cougoul; Cyril Sahyoun; Jerôme Stirnemann; Benoît Desgraz; Olivier Grosgurin; Jean-Luc Reny; Jacques Serratrice; Yves Chalandon; Marc Ansari; et al. (BMJ Open)
Introduction Sickle cell disease (SCD) is one of the most common genetic diseases in the world, annually affecting approximately 310 000 births and causing >100 000 deaths. Vaso-occlusive crisis (VOC) is the most frequent complication of SCD, leading to bone pain, thoracic pain (acute chest syndrome) and/or abdominal spasms. It is the main cause of mortality in patients with SCD, reducing life expectancy. Hyperbaric oxygen therapy (HBOT) is a safe and well-established method of increasing tissue oxygen delivery immediately by up to 10-fold to 20-fold. In the context of VOC, HBOT has the potential to limit sickling. A previous pilot study of nine patients showed the safety and potential benefits of HBOT on VOC-induced pain. Our study aimed to assess the clinical safety and effectiveness of HBOT for treating VOC, its biological mechanisms of actions and its cost-effectiveness.Methods and analysis This is a multicentric, triple-blinded, randomised controlled trial. Patients aged 8 years or above with a diagnosed major form of SCD, presenting at one of the participating centres’ emergency departments (EDs) with a VOC requiring level 3 analgesia (according to WHO definition), will be eligible. Exclusion criteria are pregnancy, mechanical ventilation, previous history of stroke or prior transcranial Doppler ultrasound anomaly, contraindication to HBOT and the need for above 2 L/min of oxygen. All patients will receive the usual care for VOCs, including hydration, analgesics, normobaric oxygen therapy and when medically indicated, antibiotic therapy and/or transfusions. Within 24 hours of their arrival in the ED (or longer in specific cases), and after obtaining informed consent, patients will be randomised into the HBOT intervention group (2.0 atmosphere absolute (ATA), 90 min, FIO2=1) or the sham group (1.3 ATA, 90 min, FIO2=0.21). After their first HBOT session, patients will return to their acute-care ward. Patients in both arms will undergo a second and third session within 24–36 hours of the first, unless their Visual Analogue Scale (VAS)-pain is ≤2 without use of level 3 analgesics. The difference in the pain-VAS before and after HBOT and other outcomes will be compared between the intervention and sham groups. Our composite primary outcome will be (1) the change in global VAS-pain 6 hours after initiation of HBOT; (2) the number of patients with a VAS-pain score >4 and/or a morphine dosage >1 mg/hour intravenous after the HBOT/sham session. Other outcomes to be reported are morphine usage, length of stay, biological parameters, satisfaction, complications and cost.Ethics and dissemination Ethical approval CER Geneva 2019-01707 (last submission V.5.1, 06.15.2023). The results of the studies will be disseminated by several media, including publications in peer-reviewed international medical journals, and presentations at national and/or international conferences.Trial registration number NCT04978116.